LEGAL PROTECTION FOR THE MENTAL HEALTH OF VICTIMS IN SEXUAL VIOLENCE IN PALANGKA RAYA CITY - Jordan Marbun; Suriansyah Murhaini; Claudia Yuni Pramita (SOSIOEDUKASI, 2026)
This study examines the legal protection of the mental health of victims of sexual violence in Palangka Raya City. Sexual violence leaves a profound psychological impact on the victim, so comprehensive legal protection is needed not only for the physical but also the mental health of the victim. This study uses an empirical juridical method with a qualitative approach. The formulation of this research problem is how is the legal protection for the mental health of victims in the crime of sexual violence in the city of Palangka Raya and how are the efforts made by the Palangka Raya Police in providing legal protection for the mental health of victims in the crime of sexual violence in the city of Palangka Raya. The results of the study show that legal protection for the mental health of victims of sexual violence in Palangka Raya City has been regulated in various laws and regulations, but its implementation still faces various obstacles. Efforts made by the Palangka Raya Police include psychological assistance, coordination with related institutions, and the formation of a special unit for handling victims. This study recommends the need to strengthen an integrated victim protection system and increase the capacity of law enforcement officials in dealing with the mental health aspects of victims.